Kesehatan Mental Jamaah Haji Lansia: Antara Tantangan Dan Strategi Spiritual - Jaelani (Jurnal Kesehatan Mahardika, 2025)
Background: Elderly Hajj pilgrims (aged 60 and above) are a vulnerable group facing significant physical and psychological challenges during the pilgrimage. Environmental stressors, fatigue, and limited communication often trigger mental health issues such as anxiety and disorientation. Spirituality is believed to play a vital role as a coping mechanism in this context. Methods: This study employed a descriptive qualitative approach using literature review and narrative interviews. Participants included three elderly Hajj pilgrims and two religious guides selected through purposive sampling. Data were analyzed thematically to identify patterns in psychological challenges and spiritual coping strategies. Results: The findings revealed that elderly pilgrims experienced psychological distress, including anxiety, confusion, and physical exhaustion. However, spiritual practices such as prayer, remembrance (dzikr), and surrender to God provided emotional stability and enhanced psychological well-being. Religious guides contributed significantly by offering spiritual and emotional support throughout the pilgrimage. Conclusion: Spirituality serves as an effective coping mechanism for elderly Hajj pilgrims in managing mental health challenges. Integrating spiritual approaches into Hajj health services is recommended to improve psychological well-being and ensure a meaningful pilgrimage experience for the elderly.